-100=b+73

Simple and best practice solution for -100=b+73 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -100=b+73 equation:


Simplifying
-100 = b + 73

Reorder the terms:
-100 = 73 + b

Solving
-100 = 73 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
-100 + -1b = 73 + b + -1b

Combine like terms: b + -1b = 0
-100 + -1b = 73 + 0
-100 + -1b = 73

Add '100' to each side of the equation.
-100 + 100 + -1b = 73 + 100

Combine like terms: -100 + 100 = 0
0 + -1b = 73 + 100
-1b = 73 + 100

Combine like terms: 73 + 100 = 173
-1b = 173

Divide each side by '-1'.
b = -173

Simplifying
b = -173

See similar equations:

| 5x^2-10x^3-35x^4=0 | | m-8/4=2/8 | | c=0.9375*180 | | 2[x+1]=3x-x+2 | | 7.50x=900 | | 3+4x=28 | | 7.50x=300 | | 8x+3-10x=-2[x-2]+3 | | -1+-7=-56 | | P=2x^2+20x+320 | | 5y=850 | | 5y=805 | | P(x)=2x^3-18x | | [cos](2x)*[cos](x)= | | cos(2x)*cos(x)= | | 4(5-x)=2(10-x^2) | | d=q-c+p | | x^2-6x+9-y^2=0 | | .2s+.6s=6 | | 40x^4-20x^2-28x-21=0 | | 9y^2+2y-32=0 | | 3(9N+11)=141 | | T=C(7+AB)forA | | z^9+z^5+z^4+1=0 | | SolveT=C(7+AB)forA | | 9(-4)-4y=36 | | -7b+17=-4 | | -3[x+6]+8=35 | | 24=z+28 | | s(14s+5)=9 | | 6x-8[x+3]=-14 | | 7.50x=195 |

Equations solver categories